Genomic features of mecA-positive methicillin-resistant Mammaliicoccus sciuri causing fatal infections in pets admitted to a veterinary intensive care unit - Sacramento, Andrey G.; Fuga, Bruna; Monte, Daniel F.M. [UNESP]; Cardoso, Brenda; Esposito, Fernanda; Dolabella, Silvio S.; Barbosa, Ana A.T.; Zanella, Rosemeire C.; Cortopassi, Silvia R.G.; da Silva, Luciano C.B.A.; Lincopan, Nilton; Sellera, Fábio P. (Elsevier, 2022)
Methicillin-resistant staphylococci have become leading cause of infectious diseases in humans and animals, being categorized as high priority pathogens by the World Health Organization. Although methicillin-resistant Staphylococcus sciuri (recently moved to Mammaliicoccus sciuri) has been widely reported in companion animals, there is scarce information regarding their clinical impact and genomic features. Herein, we reported the occurrence and genomic characteristics of methicillin-resistant M. sciuri recovered from fatal infections in pets admitted to an intensive care unit of a veterinary hospital, in Brazil. Two M. sciuri strains were isolated from bronchoalveolar lavage samples collected from dog (strain SS01) and cat (strain SS02) presenting with sepsis and acute respiratory distress syndrome. Both isolates displayed a multidrug-resistant profile, whereas whole-genome sequencing analysis confirmed the presence of the mecA gene, along to genetic determinant conferring resistance to macrolides, streptogramins, aminoglycosides, and trimethoprim. For both strains, the mec and crr gene complex shared high identity (≥97%) with analogue sequences from a M. sciuri isolated from a human wound infection, in the Czech Republic. Strains were assigned to the sequence type ST52 and the novel ST74. Phylogenomic analysis revealed a broad host range association of these strains with several hosts and sources, including humans, animals, food, and the environment through different years and geographic locations. Our findings demonstrate that infections caused by mecA-positive M. sciuri strains can be a serious threat for veterinary intensive care patients and the medical staff, with additional implications for One Health approaches.
Keywords: Coagulase-negative staphylococci; Companion animals; Methicillin resistance; Staphylococcus sciuri; Veterinary critical care